Nurses' Perspectives on Patient Safety Culture - S Salavati; T Fanoosi; D Dehghan; H Tabesh (Iran University of Medical Sciences, 2013)
Abstract   Background & Aim: Health care organizations have growing recognition to patient safety for improving the quality of services. The main requirement to improve patient safety is patient safety culture. The aim of this study was to determine the current patient safety culture from the perspective of nurses working in university and private hospitals of Ahvaz city.   Material & Methods: In this analytic cross-sectional study, 142 nurses working in five academic and three private hospitals in Ahvaz city were randomly selected. Data was collected by Hospital Survey on Patient Safety Culture questionnaire (HSOPSC). The first part of the questionnaire included nurses' and organizational characteristics the second part consisted of 42 questions to evaluate 12 dimensions of patient safety culture. Data was analyzed by descriptive statistics and independent T test using SPSS-PC (v.16).   Results: The average percentage of positive responses to patient safety culture questionnaire was %55.8 %16 and %56.3 %15 in academic and private hospitals respectively. The strengths of patient safety culture in academic hospitals were related to three dimensions of organizational learning-continuous improvement (71.54%), teamwork across hospital units (76.03%), and non-punitive response to errors (81.1%) and the strengths in private hospitals were related to the dimensions of organizational learning-continuous improvement and non-punitive response to errors. The lowest score of patient safety culture was related to communications and giving feedback about errors in university hospitals (26.7%), and patient transportation in hospital and communication among units in private hospitals (33.87%). Most nurses (68.2% in private and 66.3% in academic hospitals) have not reported any events to supervisor in the past 12 months. There was no statistically significant difference between academic and private hospitals in patient safety scores.  Conclusion: Managers actions to promote safety, giving feedback in response to errors, creating an appropriate context for reporting accidents and exchange of patient information in the studied hospitals seems to be crucial.   Received: 8 Jul 2013   Accepted: 9 Oct 2013